Dementia care in Israel: top down and bottom up processes - Netta Bentur; Shelley A. Sternberg (BMC, 2019)
Abstract Dementia is one of the main causes of disability among older adults and is viewed as one of the most distressing and devastating of conditions. Dementia has a profound impact on those who suffer from the disease and on their family caregivers. In this article, we describe the added benefit of implementing top-down and bottom-up strategies in the process of influencing and developing healthcare services. We use Israel as an example to argue that breakthroughs in care implementation and development of services are more likely to occur when there is a convergence of top-down and bottom-up processes. In the first section of the article, we present the top-down plans, initiated to address the needs of people with dementia and their families. In the second section, we present examples of bottom-up projects that developed in Israel before and after the top-down plans were initiated. In the third section, we contend that it is the combination of these top-down and bottom-up strategies that led to a breakthrough and the expansion of services for people with dementia and their families, and we argue that the Israeli case study is applicable to other health systems.